Initial difficulties with breastfeeding technique and the impact on duration of exclusive breastfeeding - Gessandro Elpídio Fernandes Barbosa; Janeide M. Pereira; Marianne S. Soares; Luciana Barbosa Pereira; Lucinéia Pinho; Antônio Prates Caldeira
Abstract Objectives: the present study aimed to evaluate the influence of initial difficulties in breastfeeding on duration of exclusive breastfeeding. Methods: a prospective study with follow up of nursing mothers and their babies in the first six months of age. The studied population was randomly selected among the Brazilian public health system (SUS, Portuguese acronym) users in three hospitals. The breastfeeding observation protocol was used to collect initial data, which also included socio-demographic, prenatal assistance, delivery care, the postpartum period and the newborn variables. After hospital discharge, data were collected by phone. The multiple regression model was used for statistical analysis. Results: 175 mother-baby binomials were followed. Problems with breasts during the postpartum hospital stay (p= 0.030; OR=2.38; CI95%=1.02-5.48), maternal work outside home (p=0.027; OR=2.12; CI95%=1.03-4.31) and low maternal schooling level (p=0.017; OR=2.13; CI95%=1.10-4.06) were shown to be associated with the early interruption of exclusive breastfeeding before the child has completed 6 months of age. A family income lower than one minimum wage was a protective factor (p=0.048; OR=0.42; CI95%=0.17-0.97). Conclusions: socioeconomic aspects and difficulties in breastfeeding associated with problems with the puerperal breasts stood out as factors which restrict the duration of exclusive breastfeeding.